2002
DOI: 10.1016/s0002-9440(10)64455-0
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas Ligand Are Up-Regulated in Pulmonary Edema Fluid and Lung Tissue of Patients with Acute Lung Injury and the Acute Respiratory Distress Syndrome

Abstract: Apoptosis mediated by Fas/Fas ligand (FasL) interaction has been implicated in human disease processes, including pulmonary disorders. However, the role of the Fas/FasL system in acute lung injury (ALI) and in the acute respiratory distress syndrome (ARDS) is poorly defined. Accordingly, we investigated both the soluble and cellular expression of the Fas/FasL system in patients with ALI or ARDS. The major findings are summarized as follows. First, the soluble expression of the Fas/FasL system was assessed in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
214
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(223 citation statements)
references
References 58 publications
6
214
0
3
Order By: Relevance
“…Alternatively, a separate internal or mitochondrial pathway can mediate apoptosis via cytochrome c and caspase activation. Lung tissue from both humans with ALI and animal models of ALI demonstrate activation of apoptotic pathways in the alveolar epithelium [22,23]. Matute-Bello and colleagues reported that bronchoalveolar fluid from patients with ALI contained soluble Fas ligand (sFasL), and the concentration of sFasL at the onset of ARDS was significantly higher in patients who died [24].…”
Section: Alveolar Epithelial Cell Apoptosismentioning
confidence: 99%
“…Alternatively, a separate internal or mitochondrial pathway can mediate apoptosis via cytochrome c and caspase activation. Lung tissue from both humans with ALI and animal models of ALI demonstrate activation of apoptotic pathways in the alveolar epithelium [22,23]. Matute-Bello and colleagues reported that bronchoalveolar fluid from patients with ALI contained soluble Fas ligand (sFasL), and the concentration of sFasL at the onset of ARDS was significantly higher in patients who died [24].…”
Section: Alveolar Epithelial Cell Apoptosismentioning
confidence: 99%
“…The Fas-FasL system is thought to play a role in epithelial apoptosis in ARDS on the basis that bronchoalveolar lavage (BAL) fluids obtained from ARDS patients contain soluble Fas and FasL and induce apoptosis in lung epithelial cell line. [5][6][7][8] Involvement of BAX, a homolog of Bcl-2 and its likely proapoptotic effect on type II pneumocytes was suggested in studies of diffuse alveolar damage. 9,10 Neutrophils were found to accumulate at inflammatory sites in the lung, in pulmonary edema fluid and BAL fluid from patients with ARDS.…”
mentioning
confidence: 99%
“…The epithelial hypothesis suggests that the epithelial injury that occurs during ALI is associated with apoptotic death of alveolar epithelial cells and predicts that anti-apoptotic therapeutic agents may be beneficial in preventing or treating ALI [13,34,35]. Our results showed that caspase-3 activity was increased in lung tissue following challenge with OA.…”
Section: Discussionmentioning
confidence: 52%
“…Bardales et al [39] reported that alveolar pneumocytes isolated from humans with ALI demonstrate upregulation of the pro-apoptotic protein, Bax [39]. In addition, several lines of evidence implicate Fas and Fas ligand in alveolar epithelial cell apoptosis during ALI [13,14,34,[41][42][43]. However, this is the first investigation into the role of FoxA1 in apoptosis during ALI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation